VD_FINDINFO Décision / 2013 / 415 vom 24. November 2011 - VD Tribunal cantonal (2011)
DÉTENTION PRÉVENTIVE, PROPORTIONNALITÉ, RISQUE DE RÉCIDIVE | 212 al. 3 CPP (CH), 221 al. 1 let. c CPP (CH), 221 CPP (CH)